The cardiopulmonary benefits of physiologically based cord clamping persist for at least 8 hours in lambs with a diaphragmatic hernia - Riddington, Paige J.; DeKoninck, Philip L. J.; Thio, Marta; Roberts, Calum T.; Bhatia, Risha; Dekker, Janneke; Kashyap, Aidan J.; Amberg, Benjamin J.; Rodgers, Karyn A.; Thiel, Alison M.; Nitsos, Ilias; Zahra, Valerie A.; et al. (Frontiers in Pediatrics, 2024)
Infants with congenital diaphragmatic hernia (CDH) can suffer severe respiratory insufficiency and pulmonary hypertension after birth. Aerating the lungs before removing placental support (physiologically based cord clamping; PBCC), increases pulmonary blood flow (PBF) and reduces pulmonary vascular resistance (PVR) in diaphragmatic hernia (DH) lambs. We hypothesised that these benefits of PBCC persist for at least 8 hours after birth. Methods: At 138 days of gestation, 21 lambs with surgically induced left-sided DH ( 86GA) were delivered via caesarean section. The umbilical cord was clamped either before ventilation onset (immediate cord clamping; ICC, n=9) or after achieving a tidal volume of 4 ml/kg, with a maximum delay of 10 min (PBCC, n=12). Lambs were ventilated for 8 hours, initially with conventional mechanical ventilation, but were switched to high frequency oscillatory ventilation after 30 minutes, if required. Ventilatory parameters, cardiopulmonary physiology and arterial blood gases were measured throughout the study. Results: PBF increased after ventilation onset in both groups and was higher in PBCC DH lambs than ICC DH lambs at 8 hours (5.2±1.2 mL/min/g vs 1.9±0.3 mL/min/g; p<0.05). Measured over the entire 8-hour ventilation period, PBF was significantly greater (p=0.003) and PVR was significantly lower (p=0.0002) in PBCC DH lambs compared to ICC DH lambs. A high incidence of pneumothoraces in both PBCC (58%) and ICC (55%) lambs contributed to a reduced sample size at 8 hours (ICC n=4 and PBCC n=4). Conclusion: Compared with ICC, PBCC increased PBF and reduced PVR in DH lambs and the effects were sustained for at least 8 hours after ventilation onset.